Understanding the Hearing-Impaired Students: A Teacher’s Lived Experience in Teaching English - Antonius Setyawan; Tuminah (Program Studi Pendidikan Bahasa Inggris IKIP PGRI Pontianak, 2020)
Teaching EFL is not easy. The inadequate initial learning, the learning facilities, and the communication gap between the teacher and the students create delicate factors. They need more understanding from the teacher especially when teaching Hearing-Impaired Students (HIS). The purpose of this phenomenological study is to describe, narratively, the teacher’s lived experiences in teaching English to HIS. Several stages as the preparation for this study involved the observations at the school, the students, the teachers, and the teaching-learning processes. The data were gained by conducting in-depth interview. The guided interviewed focused on: understanding of the students, the teaching, and the treatment. The collected data were classified and coded. In conclusion, the data reveal that, the teacher understands that her students are very unique because of their hearing impairment. It makes them have difficulty in writing and speaking but they still can learn.